Relatability: the hidden force behind Black African youth employment disadvantage - Mthembu, Sifiso Wiseman (Graduate School of Business (GSB), 2025)
South Africa has very high levels of youth unemployment by global standards. In addition, its youth labour market is characterised by high levels of racial inequalities which lead to marked disparities in employment access and outcomes based on race. Studies have revealed that Black African youth in South Africa are as much as five times more likely to be unemployed than their peers from other race groups, even after differences in observable human capital characteristics have been accounted for. This inductive qualitative study sought to engage with employers from corporates in the formal sector, employer federation representatives, youth work-readiness intermediary representatives and finally, unemployed Black African graduates and matriculants, with the aim of uncovering employer preferences, behaviours and decision-making processes that might account for the vast differences in the labour market prospects of youth to the detriment of Black Africans. Drawing from multi-disciplinary theoretical perspectives such as the race and ethnicity theory, institutional racism theory, labour market segmentation theory and a blend of perspectives focusing on social processes that underpin labour market inequalities, this study found that the Black African youth labour market disadvantage is an outcome of an interplay of macro-contextual structural factors, exclusionary economic and labour market design, intra-organisational processes and a racialised corporate power structure. From an employment decision-making perspective, the key finding of the study is that Relatability is the bedrock upon which Black African youth labour market exclusion rests. It is manifested through five key processes of Self-Presentation, Confidence, Bias, Choice and Affinity, which are underpinned by Unconscious Incompetence, Contextual Apathy, Limited Social Imaginary, Short-termism and Homophily. Structurally, it rests on and is enabled by White Intra-Organisational Power Dominance, a Culture of Selective Affirmation, and Unfettered Managerial Discretion.